Donor white blood cell survival and cytokine profiles following red blood cell transfusion in Australian major trauma patients. (November 2018) - Hirani, Rena; Dean, Melinda M.; Balogh, Zsolt J.; Lott, Natalie J.; Seggie, Julie; Hsu, Jeremy M.; Taggart, Susan; Maitz, Peter; Survela, Lesley; Joseph, Anthony; Gillett, Mark; Irving, David O.
Highlights: One patient of the 11 who required a red blood cell transfusion was found to have donor white blood cell survival. Trauma patients who needed a blood transfusion showed elevated IL-6 and IL-10 cytokines. For this cohort there was no correlation between the elevated cytokine and incidence of donor white blood cell survival. This study is the first to analyze the potential of cytokines to provide a possible mechanism for donor cell survival. Abstract: Background: The potential for the co-existence of genetically disparate cells (microchimerism) and associated cytokine profiles following red blood cell (RBC) transfusion in trauma patients has not been well characterized to date. This study investigated the incidence of surviving donor white blood cells (known as transfused-associated microchimerism (TAM)) and cytokine changes following blood transfusion in trauma patients. Study design and methods: Trauma patients with an injury severity score (ISS) >12 who had been transfused between 2012–2016 with at least 5 units of RBC units over a 4 h period were recruited. Trauma patients with ISS > 12 who did not require blood transfusion were recruited as controls. The incidence of TAM was determined using a panel of insertion/deletion (InDel) bi-allelic polymorphisms. Selected pro- and anti-inflammatory cytokine profiles were analyzed using cytometric bead array. Results: The transfused cohort (n = 40) had median ISS of 28 [12–66], received a median of 11 RBC units [4–114] and had median hospital length of stay of 35 days [1–152]. Only 11 (27.5%) patients returned for follow-up blood sampling after discharge. Of these, one patient showed an InDel pattern indicating the presence of TAM. No patients in the control cohort (n = 49) showed TAM. Cytokines IL-10 and IL-6 were found to be elevated in the transfused trauma patients. Conclusion: In this cohort, TAM was found to occur in one patient of the 11 who received a blood transfusion. Elevated IL-6 and IL-10 cytokines were detected in those patients who were transfused. However, the incidence of TAM could not be correlated with the elevated cytokine profiles for this cohort.